2022
DOI: 10.32604/csse.2022.024059
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machine Based Handwritten Hindi Character Recognition and Summarization

Abstract: In today's digital era, the text may be in form of images. This research aims to deal with the problem by recognizing such text and utilizing the support vector machine (SVM). A lot of work has been done on the English language for handwritten character recognition but very less work on the under-resourced Hindi language. A method is developed for identifying Hindi language characters that use morphology, edge detection, histograms of oriented gradients (HOG), and SVM classes for summary creation. SVM rank emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One another solution to multilingualism is facial recognition and it has been reported that facial recognition based sentiment analysis has gained noticeable attention due to the advanced technology in commercial and industrial applications such as smart Master card for online transaction, health related devices, character recognition, IoT, Post Pandemic World, pain detection, criminal identification and security surveillance [49], [50], [51], [52], [53], [54], [55]. HF-CSA makes it possible to sort and utilize unstructured text of resource poor languages in order to assess customer support issues and to support consumers' satisfaction, reputation management, brand monitoring, decision support systems and market analysis.…”
Section: Sensitivity = Tp (Tp + Fn )mentioning
confidence: 99%
“…One another solution to multilingualism is facial recognition and it has been reported that facial recognition based sentiment analysis has gained noticeable attention due to the advanced technology in commercial and industrial applications such as smart Master card for online transaction, health related devices, character recognition, IoT, Post Pandemic World, pain detection, criminal identification and security surveillance [49], [50], [51], [52], [53], [54], [55]. HF-CSA makes it possible to sort and utilize unstructured text of resource poor languages in order to assess customer support issues and to support consumers' satisfaction, reputation management, brand monitoring, decision support systems and market analysis.…”
Section: Sensitivity = Tp (Tp + Fn )mentioning
confidence: 99%
“…There are currently several types of SVM, such as twin SVM [1], Gaussian SVM [2], multi-kernel SVM [3] and so on. Furthermore, SVM has been widely applied in a variety of fields, for example, handwritten hindi character recognition [4], face recognition [5], network intrusion detection [6] and breast cancer diagnosis [7], and so on. Although SVM is a common algorithm for classification problems that treats all samples equally and ignores the effect of outliers and noise on the construction of optimal hyperplanes, it fails to perform well when classifying new sets of data with fuzzy information.…”
Section: Introductionmentioning
confidence: 99%